Carrageenans from Red Seaweeds As Promoters of Growth and Elicitors of Defense Response in Plants - Shukla, Pushp S.; Borza, Tudor; Critchley, Alan T.; Prithiviraj, Balakrishnan (Frontiers in Marine Science, 2016)
Plants incessantly encounter abiotic and biotic stresses that limit their growth and productivity. However, conversely, plant growth can also be induced by treatments with various abiotic and biotic elicitors. Carrageenans are sulfated linear polysaccharides that represent major cellular constituents of seaweeds belonging to red algae (Rhodophyta). Recent research has unraveled the biological activity of carrageenans and of their oligomeric forms, the oligo carrageenans (OCs), as promoters of plant growth and as elicitors of defense responses against pests and diseases. In this review, we discuss the molecular mechanisms by which carrageenans and OCs mediate plant growth and plant defense responses. Carrageenans and OCs improve plant growth by regulating various metabolic processes such as photosynthesis and ancillary pathways, cell division, purine and pyrimidine synthetic pathways as well as metabolic pathways involved in nitrogen and sulfur assimilation. Carrageenans and OCs also induce plant defense responses against viroids, viruses, bacteria, fungi and insects by modulating the activity of different defense pathways, including salicylate, jasmonate and ethylene signaling pathways. Further studies will likely substantiate the beneficial effects of carrageenans and of OCs on plant growth and plant defense responses and open new avenues for their use in agriculture and horticultural industry.